2021
DOI: 10.14245/ns.2040774.387
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Robotic Single Position Oblique Lumbar Interbody Fusion With Bilateral Sacropelvic Fixation in Lateral Decubitus

Abstract: Single position lateral fusion reduces the need for a secondary surgery and robotic guidance allows for potentially higher accuracy of screw placement. We expand the role of robotics with a simultaneous workflow where 2 surgeons can work in single position surgery and discuss the technical feasibility of placement of S2-alar-iliac (S2AI) screws in the lateral position. A 70-year-old male presented with chronic back pain and bilateral leg pain with the left side worse than the right. He subsequently underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Navigated OLIF can also be performed with robotic assistance for posterior pedicle screw instrumentation [ 97 ]. More recently, the application of robotic and navigation-assisted OLIF in a single position has been expanded to the lumbosacral junction: OLIF at L5–S1 and posterior sacropelvic fixation [ 98 , 99 ]. Because this is a still-evolving technique, future studies investigating the long-term outcomes and cost-effectiveness of these technical advancements should follow.…”
Section: Recent Advancementsmentioning
confidence: 99%
“…Navigated OLIF can also be performed with robotic assistance for posterior pedicle screw instrumentation [ 97 ]. More recently, the application of robotic and navigation-assisted OLIF in a single position has been expanded to the lumbosacral junction: OLIF at L5–S1 and posterior sacropelvic fixation [ 98 , 99 ]. Because this is a still-evolving technique, future studies investigating the long-term outcomes and cost-effectiveness of these technical advancements should follow.…”
Section: Recent Advancementsmentioning
confidence: 99%
“…Recently, Kotani et al ( 40 ) found that single-position OLIF can provide a comparable fusion rate, segmental radiologic alignment, and symptomatic adjacent segment degeneration to MIS-TLIF surgery. Pham et al ( 41 ) presented a novel technical report on the recommended workflow of simultaneous robotic single-position OLIF and demonstrated the'feasibility of placement of sacroiliac fixation in the lateral decubitus position. In addition, Diaz-Aguila et al ( 26 ) found that robot-assisted OLIF can reduce the operative time while ensuring accurate and timely screen placement with minimal complications.…”
Section: Discussionmentioning
confidence: 99%
“…The standard surgical procedures were performed as follows: 9,[12][13][14]17 1. After general anesthesia, the patient was placed in the left lateral decubitus position after an indwelling urinary catheter was inserted.…”
Section: Surgical Technique Of Olifmentioning
confidence: 99%